The prognostic impact of BIA-derived fat-free mass index in patients with cancer. Issue 6 (June 2021) - Cereda, Emanuele; Pedrazzoli, Paolo; Lobascio, Federica; Masi, Sara; Crotti, Silvia; Klersy, Catherine; Turri, Annalisa; Stobäus, Nicole; Tank, Maja; Franz, Kristina; Cutti, Sara; Giaquinto, Ester; et al.
Summary: Background & aims: Reduced muscle mass represents one of the top ranked phenotypic criteria for malnutrition proposed by the Global Leadership Initiative on Malnutrition. Although height-indexed fat-free mass (FFMI) thresholds have been proposed as useful surrogate measures of reduced muscle mass, the independent prognostic value of BIA-derived FFMI by bioelectric impedance analysis (BIA) in patients with cancer still needs to be fully explored. Methods: Data on body mass index (BMI), 6-month percentage of weight loss (%WL), FFMI by BIA and quality of life (QoL by EORTC Quality of Life Questionnaire [EORTC QLQ-C30]) of Italian and German patients observed prospectively until death or censoring were used (N = 1217). Patients were stratified in 5 risk categories according to a robustly validated scoring system based on BMI and %WL. Low FFMI was defined as follows: men, <17 kg/m 2 ; women, <15 kg/m 2 . Results: Reduced FFMI was found in 234 patients (19.2%). After a median follow-up of 57 months [25th-75th, 31–60], 620 patients (50.9%) had died. The study detected differences in survival between patients presenting with and without reduced FFMI (14.0 months vs. 45.1 months; P < 0.001). The fully-adjusted hazard ratio of mortality for low FFMI was 1.46 [95%CI, 1.18–1.81] (P < 0.001). Low FFMI was also independently associated with reduced QoL: fully-adjusted odds ratio, 1.50 [95%CI, 1.00–2.25] (P = 0.050). Conclusions: Reduced FFMI by BIA independently predicted survival and was associated with impaired QoL. Altered body composition should always be considered in all patients with cancer as additional phenotypic criterion of poor prognosis and BIA offers the possibility of multiple, noninvasive bedside assessments.